Evaluation of ERG Expression in Prostate Adenocarcinoma and Its Prognostic Impact in Patients Survival Rate - Hedieh Moradi Tabriz; Leila Aghapour Sabaghi; Amirreza Nabighadim; Elham Nazar; Seyed Mohammad Kazem Aghamir (Iranian Society of Pathology, 2021)
Background & Objective: Some certain markers, including prostatic specific antigen (PSA), are being used to screen prostate cancer (PC), but none of them have sufficient sensitivity and specificity for evaluation of prognosis. Currently, genetic variants have found their place in the prognosis of PC. ETS-related gene (ERG) expression and its intensity have contradictory evidence regarding ERG expression with PC incidence or associating outcome. Our purpose was to survey the relationship of ERG expression and its intensity with PC and relative clinical outcome.Methods: We studied the immunohistochemichal (IHC) expression of ERG in 101 radical prostatectomy specimens with PC of different histologic grades. All samples were chosen from pathology department of Sina hospital in Tehran-Iran from 2011 to 2018.  Positive ERG expression and its association with Gleason score, preoperative PSA, metastasis status, stage and grade of tumors was evaluated.Results: In total, ERG expression was observed in 42 cases (41.58%) and of these, 7 (16.66%) were categorized as weak, 13 (30.95%) moderate and 22(52.38%) as strong. There was no significant correlation between ERG expression and age, preoperative PSA, Gleason score, lymph node involvement, metastatic pattern, stage, and grade of the tumor (P>0.05). ERG expression frequency in the two groups of survived and expired patients was 42.85% and 0%, respectively; despite the noticeable difference, it was not statistically significance (P=0.264).Conclusion: Evaluation of ERG expression and its intensity may have no essential role as an acceptable prognostic factor in Iranian's population for anticipating whether PC itself or the outcomes accompanied. This relation is vigorously under the influence of geographical/ethnical features.